Analisis Bau, Warna, TDS, pH, dan Salinitas Air Sumur Gali di Tempat Pembuangan Akhir - Sari, Mayang; Huljana, Mifta (SCIENCE AND TECHNOLOGY FACULTY OF UNIVERSITAS ISLAM NEGERI RADEN FATAH PALEMBANG, 2019)
ABSTRACT Wells are one of the means of providing clean water originating from the soil layer which is relatively close to the surface of the ground, so it needs attention because it is easily contaminated and contaminated through seepage. Especially if the construction of the dug well does not meet the requirements. The use of clean water facilities with dug wells was also carried out by the community around TPA II in the Karya Jaya Musi 2 Village of Palembang. This study aims to determine whether the variables of odor, color, TDS, pH and salinity of dug well water around TPA II in Karya Jaya Musi 2 Palembang village meet the quality standards in accordance with Minister of Health Regulation No. 32 of 2017. Several procedures in this study include: two test parameters are physical parameters which include odor, color and total dissolved solids (TDS) and chemical parameters, namely salinity and acidity (pH). The results of the physical parameter analysis showed that the dug well water smelled, colored and had a total dissolved solids of 3.182 mg / l, while the results of the chemical parameter test were pH 5 and salinity 22 ppt. The test results showed that the quality of well water dug in the variables of odor, color, TDS, pH and salinity around the landfill did not meet the quality standard according to Permenkes RI No. 32 of 2017. Keywords : Clean Water; Final Disposal Site (TPA) II; Well Digging